Răspuns :
a-b=398
a:b=18 rest 7
a=bx18+7
(bx18-b)+7=398
bx17+7=398
bx17=398-7
bx17=391
b=391:17
b=23
a=398+23
a=421
proba:421-23=398
421:23=18 rest 7
a:b=18 rest 7
a=bx18+7
(bx18-b)+7=398
bx17+7=398
bx17=398-7
bx17=391
b=391:17
b=23
a=398+23
a=421
proba:421-23=398
421:23=18 rest 7
a-b=398
a:b=18 rest 7⇒a=18b +7
18b-b+7=398
17b=398-7
17b=391
1b=391:17
1b=23
a=18x23+7
a=414+7=421
raspuns: a=421;b=23
a:b=18 rest 7⇒a=18b +7
18b-b+7=398
17b=398-7
17b=391
1b=391:17
1b=23
a=18x23+7
a=414+7=421
raspuns: a=421;b=23